2013
DOI: 10.2322/tjsass.56.49
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Study of Throttled Operation of Rocket Engine Turbopump

Abstract: Throttled operation of turbopumps of liquid rocket engines is studied analytically. Two types of pressure drops in the propellant injector are examined, that is, the drop of gas injection and that of liquid injection. Circulation is examined in relation to throttling to operate the pump in the vicinity of the design condition. An enthalpy increase at the pump entrance is derived analytically in the circulation system. With the derived analytical relationships, throttled operating conditions are examined for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…3, 2018 ber pressure. 17,21) Under the condition of maximum throttle, when a pressure drop in the oxygen injector remains at 15%, it will drop further as throttling is reduced. This large pressure drop in injection affects the necessary pump power and operating range of the engines.…”
Section: à1=4 ð8þmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 2018 ber pressure. 17,21) Under the condition of maximum throttle, when a pressure drop in the oxygen injector remains at 15%, it will drop further as throttling is reduced. This large pressure drop in injection affects the necessary pump power and operating range of the engines.…”
Section: à1=4 ð8þmentioning
confidence: 99%
“…Several studies have been conducted on the thrust control ability of liquid rocket engines, most of which targeted hydrogen-fueled engines and bipropellant engines. [17][18][19][20][21] For example, it was found that the throttled operation of a rocket engine can degrade excessive acceleration during launch while reducing the thrust required when landing a reusable vehicle. Boccaletto conducted studies on the throttling operation of methane-fueled engines ranging from 40% to 125% when using the SC cycle and the GG cycle.…”
Section: Introductionmentioning
confidence: 99%